2022
DOI: 10.3390/ijerph192013661
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Psychological Capital of Chinese University Students during the COVID-19 Pandemic: The Serial Mediation Effect of Learning Satisfaction and Learning Engagement

Abstract: The mediating mechanism between the emotion regulation and psychological capital of university students is currently unclear. This study analyzed the serial mediation of learning satisfaction and learning engagement on the relationship between the emotion regulation and psychological capital of university students during the coronavirus disease 2019 (COVID-19) pandemic. A total of 328 undergraduates and postgraduates from universities in different regions of China were surveyed through an online questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The empirical landscape further bolsters the association between emotion regulation strategies, such as reappraisal and cognitive reappraisal, and elevated levels of psychological capital ( Tang and He, 2022 ). In line with existing literature ( Joo et al, 2016 ; Roemer and Harris, 2018 ), our study underscores the well-established relationship between psychological capital and work engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical landscape further bolsters the association between emotion regulation strategies, such as reappraisal and cognitive reappraisal, and elevated levels of psychological capital ( Tang and He, 2022 ). In line with existing literature ( Joo et al, 2016 ; Roemer and Harris, 2018 ), our study underscores the well-established relationship between psychological capital and work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research evidence has shown that effective emotion regulation strategies, such as reappraisal and cognitive reappraisal, positively relate to higher levels of psychological capital ( Tang and He, 2022 ). By managing emotions adaptively, individuals are better equipped to build their resilience, maintain a positive outlook, and develop a sense of self-efficacy and hope ( Mónico et al, 2016 ).…”
Section: The Hypothesesmentioning
confidence: 99%
“…Gross (1998) defined emotion regulation as the process through which people decide what emotions to feel, how they experience these emotions and what they do to express and control their emotions. Emotion regulation can shape learning experiences by enabling learners to increase positive and reduce negative emotions, thereby maintaining motivation for learning and improving performance (Bielak & Mystkowska-Wiertelak, 2020;Pekrun et al, 2011;Pekrun & Stephens, 2009;Tang & He, 2022). Gross (2001) proposed two predominant emotion regulation strategies: cognitive reappraisal (reappraisal) and expressive suppression (suppression).…”
Section: The Moderating Role Of Emotion Regulation In Online Pdmentioning
confidence: 99%
“…Affect, which comprises positive and negative affect ( 30 , 31 ), is closely related to PsyCap and psychological resilience ( 32–35 ). Emotion regulation refers to the capacity to manage and express emotions ( 36 , 37 ) and reflects anticipation, reactivity, and adaptation occurring after life events ( 38 ). According to the personal resource theory, positive affect is promoted by successful emotion regulation and consequently leads to the accumulation of PsyCap ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotion regulation refers to the capacity to manage and express emotions ( 36 , 37 ) and reflects anticipation, reactivity, and adaptation occurring after life events ( 38 ). According to the personal resource theory, positive affect is promoted by successful emotion regulation and consequently leads to the accumulation of PsyCap ( 36 ). Moreover, effective emotion regulation was found to promote PsyCap and reduce psychological impairment caused by the pandemic ( 39 ).…”
Section: Introductionmentioning
confidence: 99%